(3eRjd GdMUQ aj ecGJHGJ Cgd GdYUQs
(3ChdgG (B:s
(3GdMeO ddg efWb CdSfI GdCbdGe HefGLGI GdVeGFQ hHYO (B: (3abO CeQ ef JLH WGYJg hgh GdSjO CHh GdNjQ jYbhH Hf GdEeGe GdCYXe GdeJhcd Ydi Gddg Cf CUfY dg OSJhQkG ai GdecGJHGJ jchf eONdkG Edi eYQaI UOhQgG s
(3BNQgG (B:s
(3hbQHc ebUhOi hHGHc cYHJi hQDjGc jG Shdi CYR eWGdHi hdjcf gPG BNQ eG hbY GdENJjGQ Ydjg hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg hai gPG GdbOQ caGjI def EbJUQ Ydjg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs